Symposium 5: Theorising Implementation: Variation And Commonality In European Approaches To E-Learning - Cousin, Glynis; Deepwell, Frances; Land, Ray; Ponti, Marisa (Proceedings of the International Conference on Networked Learning, 2004)
From our analysis of narratives gathered from a range of actors, this paper argues that pedagogical, technological, cultural, and organisational dimensions are closely interrelated in the university system, so that the deployment of technology creates changes – or, at least, the need for them – in the other dimensions. In order appropriately to capture and help clarify the complexity of implementation, this paper explores ideas around an analytic framework with sufficient explanatory power to: i) identify the variation and commonality arising from the narrative data which our research has gathered ii) address the distinctive issues that occur at differing levels of implementation, from individual agency through to teams, faculties, institutions and the wider policy environment iii) provide some indication of why implementation proves more troublesome in some contexts than in others This paper offers an analysis of the data and presents emerging findings from the thematic analysis of our narrative data. From this, we will identify a set of generative questions to inform e-learning implementation.